2002
DOI: 10.1053/jars.2002.25259
|View full text |Cite
|
Sign up to set email alerts
|

Postmeniscectomy osteonecrosis

Abstract: In the last few years, postmeniscectomy osteonecrosis has been reported, especially in elderly patients, with low incidence, unclear physiopathology, and without long periods of follow-up. We report a case diagnosed and followed-up for a 3-year period using magnetic resonance imaging. In the initial phase, a large area of intramedullary edema was evident; after 3 months, the edema had decreased (it was no longer evident at 1 year examination) and a clearly defined area of osteonecrosis was evident with very hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 0 publications
0
31
0
3
Order By: Relevance
“…[1235610] Bone resorption study has been reported in the literature after 3 months and 8 months, respectively. [1718]…”
Section: Discussionmentioning
confidence: 99%
“…[1235610] Bone resorption study has been reported in the literature after 3 months and 8 months, respectively. [1718]…”
Section: Discussionmentioning
confidence: 99%
“…[7]. Позже в литературе патологию описывали как «постартроскопический остеонекроз» [8], «постменискэктомический остеонекроз» [9,10] и «остеонекроз в прооперированном коленном суставе» [11].…”
Section: постартроскопический некроз мыщелков бедренной и большеберцоunclassified
“…An MRI groin pain-specifi c protocol should include sequences covering the entire bony pelvis as well as higher-resolution sequences dedicated to the pubic symphysis region. A relatively outperformed model like a 1.5 T MRI unit is an adequate instrument to generate high-quality images of the pelvis, while a 3 T scanner can offer indubitable advantages in signal and resolution but is also prone to generate more imaging artifacts [ 95 ]. Images must be acquired in standard coronal, sagittal, and axial planes; however, it is important to underline that coronal oblique imaging plane performed along the anterior margin of the iliac crest is a very important sequence for optimal assessment of the rectus abdominis/adductor longus common aponeurosis at the pubic level [ 96 ].…”
Section: Imagingmentioning
confidence: 99%
“…A case series by Osbahr et al reported on eight previously asymptomatic youth baseball players who experienced a sudden acute avulsion fracture during the act of throwing [ 95 ]. Patients typically reported a sudden pain or "pop" while throwing and presented with acute pain, swelling, and tenderness, as well as decreased range of motion [ 95 ]. Plain radiographs are usually sufficient for diagnosis and most often reveal a Salter-Harris type I fracture, but fragmentation of the epicondyle may be observed.…”
Section: Medial Epicondyle Apophyseal Injuriesmentioning
confidence: 99%
See 1 more Smart Citation